Uterine Involution in Hosltein cows in the province of Carchi, Ecuador - García Díaz, Juan Ramón; Hernández Barreto, Miguel Alejandro; Vargas Hernández, Silvino (My University, 2018)
Objective. To evaluate the uterine involution in Holstein cow, under the conditions of production of the bovine dairy cattle in the province El Carchi, Ecuador. Materials and Methods. Sixty cows were selected and the time for uterine involution was determined by the recto-vaginal examination, ultrasonography and the clinical score of the regression of the uterus. The statistical parameters for each variable were determined. The effect of parity and body condition (CC) on complete uterine involution was evaluated by multifactorial ANOVA and the LSD test to compare means. Results. The clinical involution of the uterus, without taking into account the clinical score occurred at 29.86±7.71 days but considering this notation was at 42 ± 0.39 days. The uterine involution took place earlier (p<0.05) in cows with BCS ≥ 3.5 at birth than in those with BCS <3.5. In second calving cows it was at 25.17±1.32 days and it was extended (p<0.05) for the third and fourth calving. The occurrence of the dominant follicle and ovulation occur at 16.63 ± 3.83 and 27.76±7.71 days, respectively. Conclusions. The clinical involution of the uterus occurred in less time when the recto-vaginal examination was considered, compared when it was evaluated taking into account the clinical score. The uterine involution process is influenced by parity and body condition at calving.
Involución uterina en vacas Holstein en la provincia El Carchi, Ecuador
Keywords: Puerperium; Parity; Ovulation; Body Condition Score; Clinical Score; Ovarian Reactivation